Growth and membrane fluidity of food-borne pathogen Listeria monocytogenes in the presence of weak acid preservatives and hydrochloric acid - Diakogiannis, Ioannis; Berberi, Anita; Siapi, Eleni; Arkoudi-Vafea, Angeliki; Giannopoulou, Lydia; Mastronicolis, Sofia K. (Frontiers in Microbiology, 2013)
This study addresses a major issue in microbial food safety, the elucidation of correlations between acid stress and changes in membrane fluidity of the pathogen Listeria monocytogenes. In order to assess the possible role that membrane fluidity changes play in L. monocytogenes tolerance to antimicrobial acids (acetic, lactic, hydrochloric acid at low pH or benzoic acid at neutral pH), the growth of the bacterium and the gel-to-liquid crystalline transition temperature point (Tm) of cellular lipids of each adapted culture was measured and compared with unexposed cells. The Tm of extracted lipids was measured by Differential Scanning Calorimetry (DSC). A trend of increasing Tm values but not of equal extent was observed upon acid tolerance for all samples and this increase is not directly proportional to each acid antibacterial action. The smallest increase in Tm value was observed in the presence of lactic acid, which presented the highest antibacterial action. In the presence of acids with high antibacterial action such as acetic, hydrochloric acid or low antibacterial action such as benzoic acid, increased Tm values were measured. The Tm changes of lipids were also correlated with our previous data about fatty acid changes to acid adaptation. The results imply that the fatty acid changes are not the sole adaptation mechanism for decreased membrane fluidity (increased Tm). Therefore, this study indicates the importance of conducting an in-depth structural study on how acids commonly used in food systems affect the composition of individual cellular membrane lipid molecules.